Ethical Analysis Of Pat Hypotheses Through Maqasid Shariah Principles - Savitri, Dwi Anugrah; Rizka Fitriasari (Telaah Ilmiah Akuntansi dan Perpajakan, 2025)
The ethical orientation of Positive Accounting Theory (PAT) has come under increasing scrutiny, especially in contexts where moral and spiritual principles, such as those in Islamic finance, are central. Although PAT is widely recognised for its ability to explain and predict managerial behaviour, its ethical compatibility with Islamic values, particularly the Maqasid Shariah framework, remains underexplored. This study critically examines the moral dimensions of PAT’s three core hypotheses, the Bonus Plan Hypothesis, Debt Covenant Hypothesis, and Political Cost Hypothesis through the lens of Maqasid Shariah, which emphasises justice, accountability, and public welfare. Employing a qualitative approach with a systematic literature review (SLR) method, this research synthesises selected academic literature, Shariah accounting standards, and Islamic legal-philosophical texts. Thematic analysis shows that although PAT-aligned behaviours may conform to Generally Accepted Accounting Principles (GAAP), they often contradict Shariah objectives such as the protection of religion (hifz al-din), wealth (hifz al-mal), and intellect (hifz al-‘aql), by encouraging opportunism, earnings manipulation, and short-termism. The findings underscore the need to embed Shariah-based ethical values in accounting practices to ensure morally responsible behaviour. This study offers an interdisciplinary contribution by integrating conventional accounting theory with Islamic ethical thought, laying the groundwork for Shariah-compliant accounting models.